2016
DOI: 10.3310/pgfar04110
|View full text |Cite
|
Sign up to set email alerts
|

Improvement in risk prediction, early detection and prevention of breast cancer in the NHS Breast Screening Programme and family history clinics: a dual cohort study

Abstract: BackgroundIn the UK, women are invited for 3-yearly mammography screening, through the NHS Breast Screening Programme (NHSBSP), from the ages of 47–50 years to the ages of 69–73 years. Women with family histories of breast cancer can, from the age of 40 years, obtain enhanced surveillance and, in exceptionally high-risk cases, magnetic resonance imaging. However, no NHSBSP risk assessment is undertaken. Risk prediction models are able to categorise women by risk using known risk factors, although accurate indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
126
1
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 117 publications
(145 citation statements)
references
References 296 publications
3
126
1
1
Order By: Relevance
“…Women were excluded from PROCAS if they had been diagnosed with breast cancer before completing the questionnaire; cancers detected as a result of the screening test were included. In total, 57,902 women were enrolled in the PROCAS study . Unaffected women in the cohort who lived within the smaller defined Withington area (South Manchester) were subsequently invited to participate in an additional risk assessment study using DNA extracted from a saliva sample; all women with breast cancer diagnosed after completion of the questionnaire were invited to provide saliva samples and participate as cases and saliva samples were obtained from 9,956 women…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Women were excluded from PROCAS if they had been diagnosed with breast cancer before completing the questionnaire; cancers detected as a result of the screening test were included. In total, 57,902 women were enrolled in the PROCAS study . Unaffected women in the cohort who lived within the smaller defined Withington area (South Manchester) were subsequently invited to participate in an additional risk assessment study using DNA extracted from a saliva sample; all women with breast cancer diagnosed after completion of the questionnaire were invited to provide saliva samples and participate as cases and saliva samples were obtained from 9,956 women…”
Section: Methodsmentioning
confidence: 99%
“…A study was run within the Greater Manchester National Health Service Breast Screening Program to identify suitable models to assess breast cancer risk in population settings (predicting risk of cancer at screening [PROCAS]). 18 Women aged 47-73 years were invited once and recruited between October 2009 and June 2015 at the time of attendance for mammographic screening. Breast cancer risk factors were selfreported by the women via completion of a two-page paper questionnaire.…”
Section: Patientsmentioning
confidence: 99%
“…For example, recent research has suggested that other germline genetic variants may be associated with mortality in women with pathogenic mutations in the genes BRCA2 and TP53 . [38,39] Beyond gene-by-gene interactions, germline variation may have a larger influence on breast cancer mortality in populations that have different background risk factors such as ancestry (this sample was of European ancestry), or country of origin (this sample was recruited from affluent countries). Germline variation may also influence mortality by way of an interaction with treatment [40], which was not consistently available for our participants.…”
Section: Discussionmentioning
confidence: 99%
“…Previous experience in a research context suggests that embedding stratification in the existing NBSP is feasible [47] but no data exist on the effects of stratification on screening uptake and this is an important topic for further research.…”
Section: Discussionmentioning
confidence: 99%